Understanding the experiences of allergy testing: a qualitative study of people with perceived serious allergic disorders. Issue 1020 (10th August 2010) - Burton, Christopher; Irshad, Tasneem; Sheikh, Aziz
Abstract : Purpose: To investigate the experience of patients with perceived severe allergic disorders in obtaining allergen testing. Design: In-depth interviews with 20 purposively sampled adults and parents of children with, or at perceived risk of, serious allergic problems. Data were analysed thematically, drawing on Frank's classification of narratives to help interpret patient/carer accounts. Results: Accounts fell into four main groups: (i) children with anaphylaxis occurring 'out of the blue' (ii) children in whom the recognition of severe allergy by professionals was perceived as delayed; (iii) adults with anaphylaxis who adapted; and (iv) adults who remained in search of an answer. Whereas children had eventually been assessed and tested in a specialist clinic, adults had difficulty in obtaining testing, and most—including those for whom current guidelines would recommend testing—had not been tested. Participants incorporated their past experience of testing into narrative accounts, which included current ways of dealing with their allergy. They saw testing as only one component of appropriate allergy management which required interpretive expertise in professionals who ordered tests. Despite the limitations in NHS allergy testing provision, there was relatively little interest among patients/carers in using complementary and alternative providers of allergy testing. Conclusions: Patients perceived major shortfalls in relation to NHS allergy testing provision, focusing on both the availability of testing and expertise in interpreting the results. Any increased provision of testing needs to be matched by access to specialist interpretation of these tests.